The Effects of Government Policies towards Contraception Use in Women - Núñez Gough, Audrey Janet (Población y Salud en Mesoamérica)
Education is considered an important factor in the relationship between fertility and contraception use. The objective of this paper is to analyze if fertility rates in countries are reduced due to government policies, specifically, direct support towards the use of birth control methods for women relative to countries with indirect support. Therefore, this paper compares Honduras and Belize, who provides direct and indirect support towards contraceptives, respectively. First, the coefficient on nationality tells us if women in Honduras are using more birth control methods than women in Belize. Second, after running a Poisson model, even though Honduras gives direct support for contraception use and Belize gives indirect support, we found there is no difference between the birth rates in Honduras relative to Belize, .188 (p< 0.1) Third, even though Honduras gives direct subsidies for contraception and Belize gives indirect subsidies, there is no difference in the frequency of contraception use between women from Honduras relative to women from Belize, 0.567 (p<0.1). As the coefficient on nationality resulted statistically insignificant in both models, we can conclude the determinant in the reduction of fertility rates in countries is the effectiveness of their contraception programs, regardless of the type of birth control support they grant women. Governments can make their programs more successful if they complement them with schooling. These educational programs along with effective contraceptive ones, will teach girls and women the benefits that come along with limiting their reproductive behavior.